End-Users' Perspectives on Energy Policy and Technology - Huh, Sung-Yoon (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue (SI) deals with different end-users' perspectives on newly developed energy policy and technology. Although the importance of end-users' preferences is not totally new to the energy sector, this issue needs to be urgently and consistently addressed if new policies, projects, and technologies are to be introduced successfully. The eight papers included in this SI are focused on various issues such as modeling the future energy demand, household energy consumption behavior, public perceptions of new energy technologies and projects, and ICT-energy efficiency interrelationship. Some papers also analyze end-users' experiences with recently introduced energy technologies. Based on these eight articles with various topics, this SI will provide fruitful insights in assessing and forecasting the evolution of the future energy sector. I hope this SI can contribute to the increase in communication and cooperation among academic researchers as well as practitioners in energy fields.